2021
DOI: 10.1038/s41598-021-97846-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, functional and inflammatory evaluation in asthmatic patients after a simple short-term educational program: a randomized trial

Abstract: This study aimed to evaluate the clinical evolution, functional parameters and inflammatory activity of asthma in patients who submitted to an educational intervention. 58 adult patients over 18 years of age with partly controlled and uncontrolled asthma were randomized into an intervention group (IG) (N = 32) and a control group (CG) (N = 26) and evaluated for 12 weeks. The Asthma Control Test (ACT), Asthma Control Questionnaire (ACQ), Asthma Quality Life Questionnaire (AQLQ) and Beck Depression Inventory (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Regarding spirometer measurement the current study found that the guidelines interventions improved the lung function of older asthmatics patients in study group compared with control group specially in FEV,PEF after implement respiratory guidelines. This finding matched with Felix et al (2021) (38) who studied the clinical, functional and inflammatory evaluation in asthmatic patients after a simple short-term educational program and found that the interventions improved the lung function of older asthmatics. Also, Paoletti et al (2020) (39) , conducted a study about the effect of an educational intervention delivered by pharmacists on adherence to treatment, disease control and lung function in patients with asthma They found that the interventions improved the lung function of older asthmatics.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding spirometer measurement the current study found that the guidelines interventions improved the lung function of older asthmatics patients in study group compared with control group specially in FEV,PEF after implement respiratory guidelines. This finding matched with Felix et al (2021) (38) who studied the clinical, functional and inflammatory evaluation in asthmatic patients after a simple short-term educational program and found that the interventions improved the lung function of older asthmatics. Also, Paoletti et al (2020) (39) , conducted a study about the effect of an educational intervention delivered by pharmacists on adherence to treatment, disease control and lung function in patients with asthma They found that the interventions improved the lung function of older asthmatics.…”
Section: Discussionsupporting
confidence: 87%
“…2 Like many other chronic diseases, patient education is an important part of asthma management. [3][4][5] Patient education programmes that include symptom monitoring, recognising/ responding to worsening asthma (eg, via an action plan), and regular review of control, treatment and skills (inhaler technique) by healthcare professionals greatly reduce asthma morbidity in both adults and children (GINA (Global Initiative for Asthma) Evidence level 'A'). 6 In an increasingly 'connected' world, the means of accomplishing patient education via multimedia interventions is becoming more accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to treatment and to other aspects of disease management are thought to be strongly implicated in the poor level of asthma control in the general population, contributing to rates as high as 50% of observed exacerbations 2. Like many other chronic diseases, patient education is an important part of asthma management 3–5. Patient education programmes that include symptom monitoring, recognising/responding to worsening asthma (eg, via an action plan), and regular review of control, treatment and skills (inhaler technique) by healthcare professionals greatly reduce asthma morbidity in both adults and children (GINA (Global Initiative for Asthma) Evidence level ‘A’) 6…”
Section: Introductionmentioning
confidence: 99%
“…It is currently accepted that the mechanisms of airway immunity–inflammation and neuroregulation are the important pathogenesis of asthma ( 5 ). It is estimated that 300 million individuals worldwide suffer from asthma, with a projected increase of an additional 100 million individuals by 2025 ( 6 , 7 ). Substantial morbidity and annual healthcare expenditure place an immense burden on individuals and society ( 8 ).…”
Section: Introductionmentioning
confidence: 99%